2009
DOI: 10.1111/j.1399-0012.2009.01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of cryopreserved vein grafts as a conduit between the coronary vein and liver graft to reconstruct portal flow in adult living liver transplantation

Abstract: Adult-to-adult living donor liver transplantation is an alternative to donation from a deceased individual, and can help relieve the shortage of liver donations available for adult patients in Asian countries. When transplant candidates have thrombosis and deterioration of the portal vein, living donor liver transplantation is relatively contraindicated because portal veins in the grafts are short and vein grafts may not be available to reconstruct the portal vein. From June 2003 to May 2007, 82 adult living d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Table 2 summarises the 37 reported cases (1990-2018) of LGV to portal anastomosis. 9,13,22,34,38,40,45,47,52,[68][69][70][71][72][73][74] All reports were single case reports or small case series (median…”
Section: Large Left Gastric Vein To Portal Vein Anastomosismentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarises the 37 reported cases (1990-2018) of LGV to portal anastomosis. 9,13,22,34,38,40,45,47,52,[68][69][70][71][72][73][74] All reports were single case reports or small case series (median…”
Section: Large Left Gastric Vein To Portal Vein Anastomosismentioning
confidence: 99%
“…Pan, 2009 38 4 n.a. Wu, 2009 70 3 Patent, well, 21, 36, 36 months after LT Ramos, 2010 40 1 n.a. Kim, 2011 45 3 Shunt patent, long term in 2, thrombosed in 1 patient, all patients well at last follow up Ravaioli, 2011 9 3 n.a., 1 patient died, 2 alive at last follow-up Hibi, 2014 47 1 n.a.…”
Section: Combined Liver and Multivisceral Transplantationmentioning
confidence: 99%
“…19,20 In the transplant setting, there has been documented use in solid organ transplants, with several studies demonstrating its use in portal vein reconstruction, cryopreserved iliac artery for renal artery and vein reconstruction, and other reports. [21][22][23][24] A more recent study showed the successful use of cryopreserved allografts in renal vessel extension in living donor kidney transplants without late vascular complications. 25 Despite these studies, a major concern is that because cryopreservation preserves living cells, donor endothelium is subject to both cell-and antibody-mediated rejection, [26][27][28][29] which may contribute to a high failure rate.…”
Section: Discussionmentioning
confidence: 99%
“…It is relatively easy to harvest large and long vein grafts from a deceased donor in DDLT, such as common iliac veins and internal jugular veins. Although cryopreserved vein grafts are useful in long arrangements of PV reconstructions, it is difficult to prepare them because they are scarce and expensive, and their patency is controversial . Multivisceral transplantations are possible in patients with diffuse portomesenteric thromboses .…”
Section: Discussionmentioning
confidence: 99%